2008
DOI: 10.2355/isijinternational.48.161
|View full text |Cite
|
Sign up to set email alerts
|

A New Semi-analytical Model for Prediction of the Strand Surface Temperature in the Continuous Casting of Steel in the Mold Region

Abstract: In this research, a new semi-analytical model is presented for the strand surface temperature in the continuous casting of steel. Firstly with a dimensional analysis approach a general relation between the strand surface temperature and the other effective variables such as conductivity of the steel, pouring temperature, casting velocity, distance from the meniscus, volume rate of cooling water, solidus temperature and heat flux density at the meniscus is deduced. The constants appeared as coefficients or powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 15 publications
0
19
0
4
Order By: Relevance
“…[8][9][10][11][12][13][14][15] It is evident that the extreme shell thinning effects lead to strand breakouts and here is the importance of understanding shell growth mechanisms to cast peritectic steels; in addition, this steel is known for presenting more longitudinal cracks.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] It is evident that the extreme shell thinning effects lead to strand breakouts and here is the importance of understanding shell growth mechanisms to cast peritectic steels; in addition, this steel is known for presenting more longitudinal cracks.…”
Section: Introductionmentioning
confidence: 99%
“…In the mold region, the average heat flux is applied to describe the heat exchange effect in the actual domain [30]:…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
“…(6) where z is the coordinate along the round axis (z=0 at the meniscus), α is a constant (it was set to 1), 14) and qa is the local apparent heat flux density at the meniscus. It can be determined that: 15) ............. (7) where ρw and Cw are the density and the specific heat of water at the average temperature in the mold, ΔT T w is the total increase in the cooling water temperature, Pm and Hm are the perimeter and length of the mold, respectively, and Q is the volume flow rate of cooling water.…”
Section: Heat Transfer Modelmentioning
confidence: 99%
“…The program was first validated using the analytical model developed by Alizadeh et al 15) and the shell thickness profile reported in Ming et al 12) In addition, the model was validated by measuring the surface temperatures in different locations on the 410 mm diamater round billet using a pyrometer. Figure 2 compares the predicted temperature profile with the measured data points, demonstrating that the agreement between the predicted values and the pyrometer measurements is quite good.…”
Section: Heat Transfer Modelmentioning
confidence: 99%